Towards a general theory of profit-driven crimes - Naylor, Robin T. (The British journal of criminology, 2003)
This paper attempts to provide a general theoretical model and a clarified terminology by which profit-driven crimes can be understood in economic rather than in sociological terms. It proposes a typology that shifts the focus from actors to actions in a way that differs from, though is compatible with, the scripts' and situational crime approaches. Rather than focusing on a profit-driven crime as a logical sequence of actions, it deconstructs a profit-driven crime into its inherent characteristics, which differ radically according to whether a crime is predatory, market-based or commercial in nature. Among the principle characteristics are whether transfers of property occur by force, free-market exchange or fraud; whether those transfers involve redistribution of wealth, distribution of income, or redistribution of income; whether the crime occurs in a non-business, underground network or legitimate business setting; and whether the optimal response is restitution, forfeiture or compensation. This approach also permits crimes to be better assessed as to their impact on national income and economic welfare levels. It helps separate the primary offence (the illegal acquisition of criminal proceeds) from secondary ones (such as corruption, violence, tax evasion and money laundering). And it has implications for the definition and relative seriousness of various profit-driven offences. If traditional criminology has focused almost exclusively on the who' and the why', and the new situational and script approaches on the how', this paper focuses on the what' by drawing out the essential characteristics of the three major forms of profit-driven crime